Effect of the School Principal’s Management, Academic Supervision, Organizational Culture, and Work Motivation to the Teacher’s Professionalism - Ujiarto, Toto; Rusdarti, Rusdarti; R.C., Rifai; Raharjo, Tri Joko (The Journal of Educational Development, 2017)
Improving the quality of human resources requires the role of teachers as professional educators. Teachers play a very important role in improving the quality of education at school. Teacher’s professionalism is the key to the proper and successful learning process. This study aims to examine the teacher’s professionalism along with its various influencing factors. The research method used was quantitative; the population included all elementary school teachers in the District of Brebes amounting to 3,950 teachers. The number of samples was 254 teachers. Data were collected through a questionnaire, which had been tested for its validity and reliability. Path analysis was used to test the moderator variables. The results show that (1) the influence of the principal’s managerial competence on the teacher’s professionalism was proven to be accepted; (2) the influence of academic supervision on the teacher’s professionalism was proven to be accepted; (3) the influence of organizational culture on the teacher’s professionalism was proven to be accepted; (4) the influence of the teacher’s work motivation on the teacher’s professionalism was also proven to be accepted. Therefore, the professionalism of elementary school teachers in Brebes in carrying out their duties was influenced by various determinant factors including the managerial competence of the principal, the academic supervision, the organizational culture, and the teacher’s work motivation.